Performance of low-cost viscoelastic damper for coupling adjacent structures subjected dynamic loads. (2020) - Ramakrishna, Uppari; Mohan, S.C.
Abstract: The application of viscoelastic material to reduce the vibrations of various structures has been interest of many researchers from past three decades. The viscoelastic material as a damper has gained popularity for mitigating the vibrations induced on buildings due to wind or earthquake forces. Despite many viscoelastic damper models are proposed for seismic protection of buildings, still its application is not widely spread in developing countries. Hence, this study focuses on modelling and fabrication of viscoelastic damper using locally available natural rubber. A systematic and detailed analysis on the performance of fabricated damper to reduce the vibrations in buildings is carried out. For this purpose, fifteen story adjacent similar buildings are connected with viscoelastic dampers. The performance of natural rubber based viscoelastic damper to improve the seismic performance of buildings is compared with that of 3 M Viscoelastic damper. Time history analysis of buildings with and without dampers is carried out under strong ground motion record. The top story time history response of displacements values indicates that, these natural rubbers based viscoelastic dampers when coupled with adjacent similar buildings reduces the seismic response significantly.